(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The reasons why students abuse drugs are crucial information. Knowledge of the difficulties associated with drug use can be improved by employing data mining techniques, which have many advantages. The focus of this study is to examine the causes of drug abuse among Lagos's high school students using data mining methods. In February of 2021, a cross-sectional study was conducted. Four hundred teenagers and young adults were present. They were given a questionnaire to fill out about their drug use habits, the types of drugs they take, and why they take them. We found that 59.1% of students drank alcohol, 23.6 % smoked cigarettes, 15.4 % used cannabis, and 3.1% used cocaine. In addition, the performance of 5 classifiers is compared in terms of correctly classified instances (CCI), with all of them performing better than the simplest classifier (more frequent category: used drug/never used drugs) in terms of the percentage of correctly classified instances. KNN yielded the highest CCI across the board when various drugs were compared (alcohol: 82.40 percent, tobacco: 66.22 percent, cannabis: 91.16 percent, and cocaine: 94.24). Use motives obtained a higher classifier performance when it came to alcohol and tobacco use, but the opposite was true for cannabis and cocaine. Peer pressure and the community in which a teen lives are two major factors that we found to have a significant impact on that teen's drug use.